Association between traumatic life events and vaccine hesitancy: A cross-sectional Australian study. (March 2023) - Christou-Ergos, Maria; Wiley, Kerrie E.; Leask, Julie
Abstract: Objectives: We sought to identify associations between the experience of traumatic life events and vaccination intention to inform whether trauma-affected individuals require targeted interventions when addressing vaccine hesitancy. Study design: We conducted an online cross-sectional survey to identify whether direct or indirect exposure to various traumatic life events and the presence of post-traumatic stress disorder (PTSD) symptoms are associated with willingness to receive a COVID-19 vaccine in an Australian sample. Methods: A national online questionnaire was administered to a representative sample of 1050 Australian adults in September 2021. Results: Lower willingness to receive a COVID-19 vaccine was associated with direct experience of a fire or explosion (adjusted odds ratio [aOR]: 0.42; 95% confidence interval [CI]: 0.23–0.78; P  = 0.006), direct experience of severe human suffering (aOR:0.39; 95% CI: 0.21–0.71; P  = 0.002) and screening positive for PTSD symptoms (aOR:0.52; 95% CI: 0.33–0.82; P  = 0.005). Conversely, higher willingness to receive a COVID-19 vaccine was associated with indirect exposure to severe human suffering (aOR: 2.0; 95% CI: 1.21–3.22; P  = 0.007). Conclusions: Our findings suggest that the experience of traumatic events and the presence of PTSD symptoms can contribute to vaccination decisions. Our work adds to the growing recognition of the need to effectively mediate the influence of traumatic experiences on encounters within the medical setting and supports the importance of addressing the needs of trauma-affected individuals in their vaccination experiences.